Spatial Analysis of the Labour Market by Using Econometric Tools. The Case of Lower Silesia Region (Dolnośląskie voivodship) - Litwińska, Elżbieta (Comparative Economic Research. Central and Eastern Europe, 2013)
This paper presents the application of econometric techniques to examine the labour market in Lower Silesia. First the analysis was performed on a data set for variables connected with labour market recorded in poviats (NUTS 4). In order to determine the existence of spatial autocorrelation Moran’s statistics I was calculated. Then the spatial regression model was used to describe the relationship between the rate of unemployment and other variables. Next, LISA cluster maps were generated for units at NUTS 5 level. The results indicate the spatial dimension of the unemployment and its tendency to creating concentrations.